2021
DOI: 10.1177/2473974x211002547
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Indicators of Prognosis in Acute Invasive Fungal Sinusitis

Abstract: Objective The purpose of this study is to identify perioperative independent prognostic factors that are available to the consulting team to aid in determining prognosis in patients with acute invasive fungal sinusitis. Study Design Retrospective chart review of patients with biopsy-proven acute invasive fungal sinusitis from 2015 to 2018. Setting Academic tertiary care center. Methods Twenty-one patients were included from our single-center retrospective review. Kaplan-Meier graphs were created, and the Bresl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(26 citation statements)
references
References 17 publications
(56 reference statements)
0
26
0
Order By: Relevance
“…Those not reporting this information typically utilized heterogeneous time intervals, such as days from neutropenia or bone marrow transplant until diagnosis or days from symptom onset to diagnosis or admission 14,23,33,41,48,50 . When timing of disease progression was reported, the disease course occurred over days to weeks, with a large fraction of disease‐related mortalities occurring within the first 4 weeks of symptoms 27,49,51,54 …”
Section: Signs and Symptomsmentioning
confidence: 99%
See 1 more Smart Citation
“…Those not reporting this information typically utilized heterogeneous time intervals, such as days from neutropenia or bone marrow transplant until diagnosis or days from symptom onset to diagnosis or admission 14,23,33,41,48,50 . When timing of disease progression was reported, the disease course occurred over days to weeks, with a large fraction of disease‐related mortalities occurring within the first 4 weeks of symptoms 27,49,51,54 …”
Section: Signs and Symptomsmentioning
confidence: 99%
“…Some report poor prognostic associations for Aspergillus spp 7 or so‐called “atypical” (non‐ Aspergillus spp/non‐mucormycete) molds, 5 although the latter has not been consistently reproduced 56 . Others have identified 57 or suggested poorer outcomes with mucormycosis 27,68 . Culture sensitivity may be decreased for mucormycetes and non‐ Aspergillus spp/non‐mucormycete molds 60,61,64 .…”
Section: Laboratory and Microbiology Diagnosticsmentioning
confidence: 99%
“…With regards to AIFS, Aspergillus antigen has been identified as a specific marker in a setting of high clinical suspicion across multiple studies. B‐D‐Glucan (BDG), a polysaccharide cell wall component found in most fungal species, has not consistently shown to be sensitive or specific for AIFS; however, some studies have shown promise in utilizing serial testing of BDG to monitor treatment responses for some fungal disease processes 12–16 …”
Section: Discussionmentioning
confidence: 99%
“…B-D-Glucan (BDG), a polysaccharide cell wall component found in most fungal species, has not consistently shown to be sensitive or specific for AIFS; however, some studies have shown promise in utilizing serial testing of BDG to monitor treatment responses for some fungal disease processes. [12][13][14][15][16] This study sought to develop a novel scoring system that better represents the diagnostic probability of biopsy proven AIFS in suspected patients with an underlying hematologic malignancy. The results of this study corroborate previous evidence that commonly ordered ancillary tests provide objective markers for risk analysis in patients with hematologic malignancies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation